Analytical Investigation of The Performance of Fluid Viscous Damper and Lead Rubber Bearing Isolator on A Multi-Storey Building - Badhon Singha; Nafis Niaz Chowdhury; Mohammad Atiqur Rahman Sakib (Institut Teknologi Sepuluh Nopember (ITS), 2025)
Earthquakes are devastating natural events that can cause substantial structuraldamage, often resulting in collapses due to inadequate seismic design. This studyinvestigates the effectiveness of two seismic protection systems: fluid viscousdamper (FVD) and lead rubber bearing (LRB) isolation, in improving the seismicperformance of a structure. The initial research did not include any base isolatoror link damper for earthquake protection. The results were then compared to asimilar investigation of the same structure using FVD and LRB isolation.Significant differences in structural behavior were observed, with both systemsdemonstrating improved performance in mitigating seismic forces. The findingshighlight the importance of incorporating advanced damping mechanisms, suchas FVD and LRB, in building design to enhance earthquake resilience in proneregions. This study underscores the critical need for integrating such seismicprotection systems to reduce structural damage and improve safety duringearthquakes.